18F-FDOPA PET/CT accurately identifies MEN1-associated pheochromocytoma. (3rd March 2020) - Tepede, Aisha A; Welch, James; Lee, Maya; Mandl, Adel; Agarwal, Sunita K; Nilubol, Naris; Patel, Dhaval; Cochran, Craig; Simonds, William F; Weinstein, Lee S; Jha, Abhishek; Millo, Corina; et al.
Abstract : Summary: Pheochromocytoma (PHEO) in multiple endocrine neoplasia type 1 (MEN1) is extremely rare. The incidence is reported as less than 2%. We report a case of a 76-year-old male with familial MEN1 who was found to have unilateral PHEO. Although the patient was normotensive and asymptomatic, routine screening imaging with CT demonstrated bilateral adrenal masses. The left adrenal mass grew from 2.5 to 3.9 cm over 4 years with attenuation values of 9 Hounsfield units (HU) pre-contrast and 15 HU post-contrast washout. Laboratory evaluation demonstrated an adrenergic biochemical phenotype. Both 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/CT and 123 I-metaiodobenzylguanidine ( 123 I-mIBG) scintigraphy demonstrated bilateral adrenal uptake. In contrast, 18 F-fluorodihydroxyphenylalanine ( 18 F-FDOPA) PET/CT demonstrated unilateral left adrenal uptake (28.7 standardized uptake value (SUV)) and physiologic right adrenal uptake. The patient underwent an uneventful left adrenalectomy with pathology consistent for PHEO. Post-operatively, he had biochemical normalization. A review of the literature suggests that adrenal tumors >2 cm may be at higher risk for pheochromocytoma in patients with MEN1. Despite a lack of symptoms related to catecholamine excess, enlarging adrenal nodules should be biochemically screened for PHEO. 18 F-FDOPA PET/CT may be beneficial for localization in these patients. Learning points: 18 F-FDOPA PET/CT is a beneficial imaging modality for identifying pheochromocytoma in MEN1 patients. Adrenal adenomas should undergo routine biochemical workup for PHEO in MEN1 and can have serious peri-operative complications if not recognized, given that MEN1 patients undergo frequent surgical interventions. MEN1 is implicated in the tumorigenesis of PHEO in this patient.